Pengembangan Media Keran Konvensional Berbasis Portable Blution Tap Terhadap Hasil Belajar Praktik Wudlu - Anas, Khoeru (Dawuh Guru: Jurnal Pendidikan MI/SD, 2024)
The aim of developing a conventional faucet based on a portable blution tap that can be disassembled, displays local cultural characters and miniatures, fosters interest, covers material content for a short duration, can be reused according to the time needed and includes material that can increase the effectiveness of learning Islamic Fiqh, wudlu material in 3rd grade student at SD 1 Medini Undaan Kudus. This research is R&D development research using ADDIE steps. The number of research subjects was 20 students. The research results show 1) teachers and students need conventional taps based on portable blution taps that can be disassembled; display local cultural characters and miniatures; cultivate interest; covers material content with a short duration; provide something new; covers material according to the syllabus; assessment of intellectual potential which includes factual, conceptual, procedural and metacognition knowledge by understanding, memorizing, applying, analyzing, formulating proposals and evaluating using written, oral and assignment test techniques equipped with pretest and post test menus as well as practical tests using media; 2) the form of development in the form of conventional tap media based on portable blution taps through the steps of analysis, design, development, implementation and evaluation; and 3) conventional taps based on portable blution taps have been proven to be effective in improving learning outcomes with a significance value (2-tailed) of 0.000, p<0.05 and a post test significance value (2-tailed) of 0.000, p<0.05